From the Editor. Issue 2 (4th July 2016) - Scott, John C.
Abstract : The goal of focal articles in Industrial and Organizational Psychology: Perspectives on Science and Practice is to present new ideas or different takes on existing ideas and stimulate a conversation in the form of comment articles that extend the arguments in the focal article or that present new ideas stimulated by those articles. The two focal articles in this issue stimulated a wide range of reactions and a good deal of constructive input.